2015
DOI: 10.7150/jca.10819
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Roles of Squamous Cell Carcinoma Antigen and 18F-FDG PET/CT in Suspected Recurrence of Cervical Squamous Cell Cancer

Abstract: Purpose: To assess the clinical value of FDG PET/CT and evaluate the complementary roles of serum squamous cell carcinoma antigen (SCCAg) and FDG PET/CT in the diagnosis of suspected recurrent of cervical squamous cell cancer. Methods: Serum SCCAg levels were retrospectively reviewed in patients previously treated for cervical squamous cell carcinoma, who had suspected recurrence of cervical cancer and who had undergone FDG PET/CT scans. The clinical impact of elevated SCCAg (>1.5 ng/ml) and negative SCCAg (≤1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…In a comparative study between 18 F-FDG PET and CT/MRI, it was reported that 18 F-FDG PET was superior to CT in detecting small metastatic lymph nodes, whose principle is based on increased glycolysis levels in tumor cells 31 . Our study demonstrated a good overall patient-based sensitivity, accuracy, PPV and NPV of 18 F-FDG PET/CT in detecting recurrent cervical cancer that are consistent with previous studies 16 - 18 , 22 . However, the specificity is lower (70.6%) compared to those studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In a comparative study between 18 F-FDG PET and CT/MRI, it was reported that 18 F-FDG PET was superior to CT in detecting small metastatic lymph nodes, whose principle is based on increased glycolysis levels in tumor cells 31 . Our study demonstrated a good overall patient-based sensitivity, accuracy, PPV and NPV of 18 F-FDG PET/CT in detecting recurrent cervical cancer that are consistent with previous studies 16 - 18 , 22 . However, the specificity is lower (70.6%) compared to those studies.…”
Section: Discussionsupporting
confidence: 90%
“…Another reason that could explain this is the inclusion of CEA in the study that accounted for most of the false positive results. False positive results have also been reported in several previous reports and these results are explained by physiological hypermetabolism and reactive lymph nodes 8 , 17 , 18 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…SCCA has been identified as a tumour marker in the diagnosis and treatment of cervical cancer. An increased level of SCCA was found to correlate with cervical cancer recurrence and lymph node metastasis (Hu et al 2015;Li et al 2015b). It is a typical tumour marker that is of clinical value in uterine cervical cancer.…”
Section: Squamous Cell Carcinoma Antigenmentioning
confidence: 99%
“…An increased level of SCCA was found to correlate with cervical cancer recurrence and lymph node metastasis (Hu et al . ; Li et al . ).…”
Section: Tumour‐associated Antigens For Cancermentioning
confidence: 99%